Adsorptive purification of ether-aldehyde fraction by natural adsorbents - Melnyk (Tkachuk), Nataliia; Melnyk, Zinoviy; Shevchenko, Oleksandr (My University, 2013)
The authors proposed an effective method of processing EAF by using cheap local adsorbents: palygorskite and hydromica, which have high adsorptive properties, could be re-generated and recycled, and deposits of which are developed in Ukraine.
Keywords: natural adsorbents; palygorsite; hydromica; ether-aldehyde fraction; природні адсорбенти; палигорськіт; гідрослюда; ефір-альдегідні фракції; кафедра процесів і апаратів харчових виробництв; кафедра теплоенергетики та холодильної техніки